Estimating abundance in unmarked populations of Golden Eagle - Stien, Jennifer; Audun, Stien; Tveraa, Torkild; Rød-Eriksen, Lars; Eide, Nina (Zenodo, 2022)
1. Estimates of species abundance are of key importance in population and ecosystem level research but can be hard to obtain. Study designs using camera-traps are increasingly being used for large-scale monitoring of species that are elusive and/or occur naturally at low densities. 2. Golden eagle (Aquila chrysaetos) is one such species, and we investigate whether existing large-scale monitoring programs using baited camera-traps can be used to estimate the abundance of golden eagles, as an alternative to traditional labour-intensive searches for active territories and nest sites during the breeding period. 3. The camera-trap data allowed two measures of abundance to be estimated within each of four main study areas in mid and northern Norway; occupancy was measured as the probability of camera site use, and population size was measured as the number of eagle individuals using the camera sites within a study area. Spatial and temporal patterns in occupancy and population size were explored and evaluated against independent estimates of the breeding pair density in the study areas. 4. Annual estimates of golden eagle occupancy showed low precision, while estimates of population size were more precise in relation to both estimated and anticipated abundance fluctuations. Estimates of population size may therefore be suitable for monitoring within study area temporal abundance trends, while estimates of occupancy seem unsuitable for such in golden eagles. Across study areas, patterns in both average occupancy and average population density estimated from population size, were consistent with the spatial pattern in average breeding pair densities (r = 0.99, and r = 0.89 respectively). This suggests that camera-trap based estimates of occupancy and population density reflect territory density at large spatial scales. In conclusion, our results suggest that baited camera-traps can be a cost-effective strategy for monitoring the abundance of golden eagles. Please see the published article for details regarding how the ...